Hubungan Pendayagunaan Zakat Produktif Dengan Kesejahteraan Mustahiq Laznas Yatim Mandiri Cabang Lamongan. - Robbani, Burhanuddin (Universitas Negeri Surabaya, 2019)
Zakat is one of the instruments in Islamic economics that has the potential and benefits to overcome poverty and realize public welfare. In optimizing the potential and benefits, productive utilization of zakat is needed. This study aims to determine the relationship between the utilization of productive zakat with mustahiq welfare on laznas yatim mandiri Lamongan branch. This research is quantitative descriptive. The number of samples used in this study were 10 respondents from the mustahiq recipients of the assistance of the utilization of productive zakat in 2018 and using the Saturated Sampling technique. The results of this study indicate that there is a very strong relationship between the variables of the utilization of productive zakat with the mustahiq welfare variable. A very strong relationship between the two variables is known through the Pearson Product Moment correlation test. Based on the results of the Pearson Product Moment correlation test, the Pearson correlation value is 0.817. Then it can be concluded that there is a very strong relationship between the variables of the utilization of productive zakat with the welfare variable mustahiq Laznas Yatim Mandiri Lamongan branch